An Assessment Of Thematic Contents Of Nigerian National Dailies: A Content Analysis Approach - Aderogba Adeyemi (The Journal of Studies in Language, Culture and Society, 2024)
Nigeria media industry is one of the most vibrant and diversified media industry in African continent. The industry has a relatively long history. This study aims to examine the focus of the print media in line with agenda setting and gate keeping functions of the mass media in the face of all of the challenges facing the country. The importance attached to subjects covered by the selected newspapers is determined by the frequency of coverage. Content analysis is the research method adopted for the study. It was discovered that that economy, politics, sport and international news were regarded as the most important subjects with 26.5%, 23.6%, 7.4% and 5.9% of the newspapers’ contents respectively. The share of newspapers’ contents on terrorism was 1.4% while corruption has a meagre 0.9% share. There is need for re-orientation of the media practitioners in the face of the current challenges of Nigeria as a nation. The press needs to accord priority to matters that are considered germane to national development. There is dire need for a radical shift in the traditional focus of Nigerian mass media.